Analisis Persediaan Bahan Baku Bleaching Earth Dengan Metode Economic Order Quantity Pada PT Salim Ivomas Pratama, Tbk Surabaya - HM, Gatot Basuki; Syahry, Muhammad Alfy (Journal of Research and Technology, 2025)
PT Salim Ivomas Pratama Tbk, Surabaya is a company engaged in the cooking oil, margarine and shortening industry which has a large enough production in Indonesia, basic raw materials CPO (Crude Palm Oil) and supporting materials such as Bleaching Earth. So it is not uncommon for PT Salim Ivomas Pratama to experience problems in raw material inventory. In the raw material purchasing system, PT Salim Ivomas Pratama, Tbk Surabaya uses an application automation system to facilitate the work of the PPIC division. By using the application automation system, it is not uncommon to experience problems with the actual stock of raw materials supporting the production of cooking oil. In overcoming this, raw material purchase data in the previous period becomes a reference for managing future purchases of Bleaching Earth raw materials. This study aims to determine the optimize of quantity and frequency, calculate total cost, determine the Safety Stock and reorder Point, and compare the total cost of Bleaching Earth raw material inventory company policies using the Economic Order Quantity method.